Continuous Relevance to ‘Unspeakable Wrongness’ in Orwell’s A Hanging: A Transitivity Analysis - Alam, Md (Advances in Social Sciences Research Journal, 2020)
ABSTRACT: This paper is an interdisciplinary study of Orwell’s queer-literary genre piece i.e. “A Hanging” with an insight into the “unspeakable wrongness” across that 1931short story / essay by the application of Halliday’s linguistic tool of “Transitivity”. The functional linguistic theory of transitivity is very instrumental in exploring “ideational meaning” about the “on-goings” of characters’ material and mental world as expressed and documented in literature. Albeit comparatively less noticed, Orwell’s “A Hanging” is a superb experiential documentation of his intolerance and disapproval of all unspeakable wrongness in all forms found in “colonialism”, “imperialism”, and “capital punishment”, discovery of all of which through the story has an extended significance and current century relevance. The study comes up with a convincing “cosmopolitan call” for the abolishment of capital punishment. Orwell goes as a narrator mentally aloof from his imperialist fellows and stands as one “odd out” with a deciphered “anti-imperialistic” impulse inside him which marks out colonialism as the very wrong “metamorphosing” power that is in itself demoralizing and makes it a huge impossibility of “equity” among universal humanity. Orwell ended up with a “Geliliolic discovery” of imperialism paving the way of only “oppression and deprivation” of the colonized and injecting a “generic moral decay” inside them; so Orwell cuts his professional “cohortship” with this giant, wrong, inhuman system that practices far-fetched, unconvincing “power imbalance” on earth by taking away the powerless races’ “freedom of speech”, and that bursts into a large scale of “moral decay” and “hollowness” of human hearts.